2(h-2)=-10

Simple and best practice solution for 2(h-2)=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(h-2)=-10 equation:



2(h-2)=-10
We move all terms to the left:
2(h-2)-(-10)=0
We add all the numbers together, and all the variables
2(h-2)+10=0
We multiply parentheses
2h-4+10=0
We add all the numbers together, and all the variables
2h+6=0
We move all terms containing h to the left, all other terms to the right
2h=-6
h=-6/2
h=-3

See similar equations:

| 13x-12=129 | | 3x+4=7x-68 | | -5(p+4)=p-(8-p) | | 40+85+x=180 | | 40+85+x=140 | | 1=7x−3(3x−7) | | -45+25=-5p+9p | | (7x-22)=8 | | 4(x+9)=-30 | | 4x+10+13x-5+56=180 | | 2(-4x)+6=40-8x | | (-x+3)6+3x=-3 | | 3x-5x-12=1x-88-5 | | 928n-7=(4-) | | 2x^2+26=20x | | 30=-10u-6+4u | | -90=-10-4n | | 14+28x=96 | | ⅙(7x-22)=8 | | -3(1+8n)=8n=23+2n | | -3(1-8n)=8n=23+2n | | 15d-30=150 | | f(-4)=8+4•-4 | | -19=9x+8 | | 2a+4=-16 | | 3(4x+2)+4=6(2x-4)+8 | | -7k-8k=52-7 | | 6x+7(x+20)=23+13x-9 | | 8x-2x=10+15 | | 15+d=30 | | 3(4x+12)+4=6(2x-4)+8 | | 8(x+2)-1=5(x+3) |

Equations solver categories